PTU-030 Number of Significant Polyps Detected Per Six Minutes of Withdrawal Time at Colonoscopy (SP6): A New Measure of Colonoscopy Efficiency and Quality. (17th August 2016) - Rameshshanker, R; Wilson, A; Tsiamoulos, Z; Tekkis, P; Saunders, BP
Abstract : Introduction: There is an increasing focus on quality, safety and efficiency of colonoscopy procedures. Colonoscopic efficiency could be defined as the ability to detect clinically relevant pathologies with a minimum expenditure of time and effort without compromising the safety of the procedure. Adenoma Detection Rate (ADR) is considered as a surrogate marker for quality of colonoscopic examination. However, ADR does not take into account sessile serrated polyps/adenomas (SSP/A) or the efficiency of detection. We therefore propose a new measure of colonoscopy efficiency the SP6 that can be used to evaluate both individual endoscopist's performance and to compare different detection interventions. Our objective was to assess the SP6 for an individual colonoscopist during standard and Endocuff –assisted colonoscopy (EAC) Methods: A prospective service evaluation of screening colonoscopies was performed by an experienced endoscopist between October 2014 and September 2015. For consecutive colonoscopies, patient demographics and procedural data were collected. Results: 96 patients had screening colonoscopy during this period. The median age was 65 years (55–74 years). A distal disposable attachment such as Endocuff Vision TM was used at the endoscopists' discretion. 49 patients had Endocuff Vision-assisted colonoscopy and the remainder had standard colonoscopy. Figure 1 summarises the main findings. There was no significant difference in caecal intubation time and withdrawal time between the two groups. Both ADR and SP6 were significantly improved and SP6 demonstrated that EAC appears to significantly improve colonoscopy efficiency with approximately twice as many pre-cancerous lesions detected and removed per 6 minutes of withdrawal time (1.11 vs 0.6, p = 0.004). Conclusion: From this preliminary data an SP6 (colonoscopy efficiency metric) appeared significantly higher when Endocuff Vision TM is used. An SP6 >1 can be achieved in the context of bowel cancer screening FOBT positive colonoscopy and may act as a new benchmark to demonstrate high quality examinations. Disclosure of Interest: None Declared